Studi Eksperimen Biomassa Padat Sebagai Bahan Bakar Alternatif Menggunakan Campuran Limbah Pertanian - Annisa, Rullie; Wahyuni, Sri; Irawan, Ibnu; Anam, Sayidil (Universitas Trunojoyo Madura, 2022)
Biomass is one of the agricultural wastes that can be used as a substitute for alternative fuels. The biomass needs to be converted into briquettes first, so that it becomes an environmentally friendly fuel. Corn cobs and rice straw are the most common types of agricultural products found in East Java, therefore the potential for alternative fuels that will be obtained will also be higher. This research aims to determine the characteristics of solid fuels (briquettes) including: calorific value of briquettes, water content of briquettes, ash content of briquettes and drop test on briquettes using a mixture of corn cobs and rice straw. The variation of the mixture between corn cobs and rice straw is 1 kg, where 1 kg of corn cobs and straw using a mixture ratio of 90%:10%, 80%:20%, 70%:30% and 60%:40% using starch adhesive of 0.001 kg. In addition, it uses two pressure variations, namely: A = 2500 kPa and B = 5000 kPa which are used in briquettes. The results of the research on the characteristics of briquettes such as: The highest calorific value using a mixture of 90% corn cobs and 10% rice straw was obtain at 5546.74 cal/gram. The most optimal moisture content using a suppression load of 5000 kPa using a mixture of 90% corn cobs and 10% rice straw obtained a value of 11.30%. The optimal ash content produced also uses a suppression load of 5000 kPa by using a mixture of 90% corn cobs and 10% rice straw to obtain a value of 20.58%. While the drop test on briquettes using a pressing load of 5000 kPa by using a mixture of 60% corn cobs and 40% rice straw obtained a value of 11.10%, a large reduction in particle size when applied from a height.